(untitled) (Physical Education, Health and Social Sciences, 2025)
In the last decade, several states have used force against non- state actors in the territory of another state, and if the rules remain unclear, states could abuse this principle to stretch the limits of the use of force. which poses a problem for the stability of the international order. This paper will therefore examine the question of when the use of force in self-defence against a non-state actor can be lawful from a jus ad bellum perspective. As a first question, it must be identified what the current difficulties are concerning the application of the self-defence framework to non-state actors. The question when the use of force in self- defence against a non-state actor can be lawful. can essentially be divided into two parts. namely, an assessment of Article 51 of the UN Charter and the principles of necessity and proportionality. and a so-called “second layer’ of analysis of the principles of necessity and proportionality. This second layer of analysis is necessary to determine when force can be used within the territory of another state (as opposed to against another state, as in the classic state-to-state situation).